Clinical and genetic characterization of PYROXD1‐related myopathy patients from Turkey. Issue 6 (10th March 2021) - Daimagüler, Hülya‐Sevcan; Akpulat, Ugur; Özdemir, Özkan; Yis, Uluc; Güngör, Serdal; Talim, Beril; Diniz, Gülden; Baydan, Figen; Thiele, Holger; Altmüller, Janine; Nürnberg, Peter; Cirak, Sebahattin
Abstract: Congenital myopathies (CMs) are a heterogeneous group of inherited muscle disorders characterized by muscle weakness at birth, while limb‐girdle muscular dystrophies (LGMD) have a later onset and slower disease progression. Thus, detailed clinical phenotyping of genetically defined disease entities are required for the full understanding of genotype–phenotype correlations. A recently defined myopathic genetic disease entity is caused by bi‐allelic variants in a gene coding for pyridine nucleotide‐disulfide oxidoreductase domain 1 ( PYROXD1 ) with unknown substrates. Here, we present three patients from two consanguineous Turkish families with mild LGMD, facial weakness, normal CK levels, and slow progress. Genomic analyses revealed a homozygous known pathogenic missense variant (c.464A>G, p.Asn155Ser) in family 1 with two affected females. In the affected male of family 2, we found this variant in a compound heterozygous state together with a novel frameshift variant (c.329_332delTCTG, p.Leu112Valfs*8), which is the second frameshift variant known so far in PYROXD1 . We have been able to define a large homozygous region in family 1 sharing a common haplotype with family 2 in the critical region. Our data suggest that c.464A>G is a Turkish founder mutation. To gain deeper insights, we performed a systematic review of all published PYROXD1 ‐related myopathy cases. Our analysis showed that the c.464A > G variant was found in 87% (20/23) of the patients and that it may cause either a childhood‐ or adult‐onset phenotype, irrespective of its presence in a homozygous or compound heterozygous state. Interestingly, only four patients had elevated CK levels (up to 1000 U/L), and cardiac involvement was found in few compound heterozygous cases.